Chemical tagging and customizing of cellular chromatin states using ultrafast trans-splicing inteins - David, Yael (2015)
Post-translational modification of the histone proteins in chromatin plays a central role in epigenetic control of DNA-templated processes in eukaryotic cells. Developing methods that enable the structure of histones to be manipulated is therefore essential to understand the biochemical mechanisms underlying genomic regulation. Here we present a synthetic biology method to engineer histones bearing site-specific modifications on cellular chromatin using protein trans-splicing. We genetically fused the N-terminal fragment of ultrafast split-intein to the C-terminus of histone H2B, which upon reaction with a complementary synthetic C-intein, generated labeled histone. Using this approach, we incorporated various non-native chemical modifications to chromatin in vivo with temporal control. Furthermore, the time and concentration dependence of protein trans-splicing performed in nucleo enabled us to examine differences in the accessibility of the euchromatin and heterochromatin regions of the epigenome. Finally, we used protein trans-splicing to semi-synthesize a native histone modification, H2BK120 ubiquitination, in isolated nuclei, and show that this can trigger downstream epigenetic cross-talk of H3K79 methylation.